MONOSEMPTOMATİK KLEINE-LEVIN SENDROMU: Bir Olgu Sunumu - KARADENiZ, Derya; ERDEM, Enis; GURDAL, Ayça; PELiN, Zerrin; OZTURK, Levent; KAYNAK, Hakan (Cerrahpaşa Medical Journal, 2014)
Background.- Kleine-Levin syndrome is characterized by recurring episodes of hypersomnia, mental disturbances and abnormal behaviour including hyperphagia and hypersexuality. The episodes start suddenly generally after a mild viral infection, mild head injury or sometimes after a psychological stress. They last few days to several weeks and end abruptly. Between the episodes, there is no sleep disturbance and patients are physically and mentally normal. Patients sleep as long as 18 to 20 hours of the day during the episode. Hyperphagia and/or hypersexuality. are in compulsive manner. Mental disturbances include, irritability, feeling of unreality or confusion. Recently, monosymptomatic and atypic forms of the syndrome were reported. In monosymptomatic form, hypersomnia occurs without hyperphagia and hypersexuality. Atypical Kleine-Levin Syndrome includes the forms where one of the symptom is replaced by an opposite one. Observation.- The clinical course of 19 year old boy with recurrent 3 episodes of hypersomnia and mental disturbances during a period of 3 months was presented. Episodes were occurred after mild viral infections or psychological stress. Electroencephalographic, and polysomnographic data supported the diagnosis of "Monosymptomatic Kleine Levin Syndrome" and no episode has occurred with the prophylactic treatment of Lithium carbonate during last 6 months period.